Growth Indices of Exclusively Breastfed Until 6 Months Age and Formula-Fed Infants in Southwest of Iran - Malekzadeh, Jan-mohamad (Int J Prev Med, 2019)
BACKGROUND: Formula milk is prepared as a nutritional substitution for human breast milk, but because of biologic and constituent differences, it might cause obesity and growth disorders in infants. In this study, we compared the growth pattern of formula-fed and breastfed infants living in Yasuj, southwest of Iran. METHODS: Infants 7–14 months of age in southwest of Iran were classified as exclusively breastfed (n = 200) and formula-fed (n = 200) in their first 6 months of life. Growth velocity and Z-scores of weight for age, length for age, weight for length, and head circumference were estimated using WHO Anthro Plus software (2010) and SPSS Version 19 (SPSS Inc., Chicago, IL, USA) using World Health Organization reference for growth data. RESULTS: The study showed that Z-score of length for age and head circumference for age at the birth were significantly lower in formula-fed group than exclusively breastfed group (P < 0.05), but the Z-score of weight for length did not differ significantly. At the sixth month of age, Z-score of weight for length was significantly higher in formula-fed group (P < 0.05), but Z-score of length for age had no significant difference and Z-score of head circumference was higher in exclusively breastfed group yet (P < 0.05). Growth velocity, prevalence of obesity, wasting, underweight, and stunting did not differ between two groups. CONCLUSIONS: Our findings suggest that formula feeding can lead to greater weight gain and may help the catch up of length, but evidences are not convincing enough to suggest the formula as an obesogenic feeding in the studied area. To make a conclusion, we suggest comparing the privileged and unprivileged areas and controlling for confounding variables including family hygiene and infant feeding practices between formula-fed and breastfed infants.